Language Diversity and Potential Conflict in Kerinci Community - Fernanda, Sinza; Fitriani, Mulya (Contemporary Society and Politics Journal, 2022)
The purpose of writing this work is to find out and describe what multicultural or linguistic diversity is in Kerinci and to find out what are the good and bad impacts of language diversity in Kerinci. This research is research using a descriptive qualitative method. The data collection technique, in this case, is using library research or other news related to the research title. The data analysis technique used by the author means content analysis. The author can obtain that the existence of the diversity of languages ​​in Kerinci is not to divide one another but to teach them how to respect each other, respect each other between one language if there is a division caused by language if they are differences. The solution is, of course, to start from themselves how to respect each other, appreciate every diversity of languages and also other diversity regardless of the diversity, instill Bhineka Tunggal Ika, which is the motto of the country, not discriminating between friends who are around us, and also by using the nation's unifying language, namely Indonesian, especially in educational institutions must apply Indonesian in the educational environment and also continue to instill in students mutual respect among the diversity that exists. After starting with themselves then, they begin to socialize with others.